Kelayakan dan Strategi Pengembangan Usaha pada Outlet Ayam Goreng Waralaba dan Mandiri - Bambang Widuri; Amiruddin Saleh; Nurheni Sri Palupi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
The key to the success of small and medium enterprises located in the possession of knowledge, courage and sincerity in running the business. Currently, in order to minimize the risks that may arise, many small businesses, especially entrepreneurs, using the franchise system (franchise) as a means to develop their business. Failure in business franchise can be traced through several aspects, namely finance, management and marketing aspects. The purposes of the study are: (1) to describe the feasibility of fried chicken business with franchise and independent system, (2) to describe the perception of consumers towards the products of fried chicken business with franchise and independent system, (3) to develop appropriate strategies for developing franchise and/or independent system. The study was conducted at franchised/independent outlet located Bogor regency. Respondent has been collected by purposive sampling with 124 respondens. The experiment was conducted from February to March 2012. Kind of data processing technique we used was Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B / C), Payback Period (PBP), Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE), Strength, Weaknesses, Opportunities and Threats (SWOT) and Quantitative Strategic Planning (QSP) analysis system. Based on feasibility analysis, both fried chicken business with franchise and independent systems are feasible to be implemented. Franchise system offers more opportunity to get higher and faster returns, as well as to reach PBP faster than independent system. Furthermore, fried chicken business with franchise system shall be easier to get the trust of consumers because that system is more practical and besides, that system also offers cheaper price which will drive someone to reach PBP and return on capital faster. The reason of consumer to buy product are price, practice, and higiene. Based on the results of the matrix QSP fried chicken franchise, earned the most interesting strategy to be applied is to maintain customer loyalty, while independent business is improving the quality of products and services.The key to the success of small and medium enterprises located in the possession of knowledge, courage and sincerity in running the business. Currently, in order to minimize the risks that may arise, many small businesses, especially entrepreneurs, using the franchise system (franchise) as a means to develop their business. Failure in business franchise can be traced through several aspects, namely finance, management and marketing aspects. The purposes of the study are: (1) to describe the feasibility of fried chicken business with franchise and independent system, (2) to describe the perception of consumers towards the products of fried chicken business with franchise and independent system, (3) to develop appropriate strategies for developing franchise and/or independent system. The study was conducted at franchised/independent outlet located Bogor regency. Respondent has been collected by purposive sampling with 124 respondens. The experiment was conducted from February to March 2012. Kind of data processing technique we used was Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B / C), Payback Period (PBP), Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE), Strength, Weaknesses, Opportunities and Threats (SWOT) and Quantitative Strategic Planning (QSP) analysis system. Based on feasibility analysis, both fried chicken business with franchise and independent systems are feasible to be implemented. Franchise system offers more opportunity to get higher and faster returns, as well as to reach PBP faster than independent system. Furthermore, fried chicken business with franchise system shall be easier to get the trust of consumers because that system is more practical and besides, that system also offers cheaper price which will drive someone to reach PBP and return on capital faster. The reason of consumer to buy product are price, practice, and higiene. Based on the results of the matrix QSP fried chicken franchise, earned the most interesting strategy to be applied is to maintain customer loyalty, while independent business is improving the quality of products and services.